The Street food snacking habits, physical activity, and electronic media exposure in relation to obesity in elementary school students - DWI SYAKIRAH, Anggun; MELVA DIANA, Fivi; RESMIATI, _ (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction Obesity is caused by an imbalance between incoming energy due to the consumption of more calories than energy expended. Excessive fat accumulation has serious and long-term health effects. This can be supported by lifestyles such as consumption of roadside snacks that are high in sugar, salt, and fat, but low in micronutrients and fiber. This study aims to determine the characteristics of respondents and analyze the relationship of street food snacking habits, physical activity, and exposure to electronic media with the incidence of obesity in elementary school students at SD Adabiah Kota Padang in 2023. Methods Research with cross sectional design. The population in this study were students of SD Adabiah Padang grades 1-5 with a total sample of 141 students, selected by proportional random sampling technique. Data on street food snacking habits and exposure to electronic media were obtained using a questionnaire, physical activity measured by PAQ-C (Physical Activity Questionnaire for Children), and obesity measured by IMT/U. Data were analyzed using the Chi-Square test. Results The number of respondents with obese nutritional status (19.9%), frequent street food snacking habits (62.4%), less physical activity (65.2%), and high exposure to electronic media (53.9%). Statistical test results showed that there was no significant relationship between street food snacking habits (p-value=0.281), physical activity (p-value=0.443), and exposure to electronic media (p-value=0.701) with the incidence of obesity in elementary school students. Conclusion The results showed no association between street food snacking habits, physical activity, and exposure to electronic media with the incidence of obesity in elementary school students.